Digital Literacy Competencies of Students in Evaluating the Accuracy of Information on the Internet: A Case Study of Library and Information Science Students - Hana Kamilah; Elva Rahmah (Darul Yasin Al Sys, 2026)
The rapid growth of digital technology has expanded access to information while increasing the risk of misinformation and inaccurate online content. This condition requires students to develop adequate digital literacy competencies to evaluate the credibility and accuracy of information obtained from the internet. This study aims to describe the digital literacy competencies of Library and Information Science students at Universitas Negeri Padang in evaluating information accuracy based on four dimensions: digital skills, digital ethics, digital culture, and digital safety. A descriptive quantitative approach was employed, involving 70 students selected through simple random sampling. Data were collected using a questionnaire and analyzed through descriptive statistics. The findings indicate that students’ digital literacy level was categorized as very high, with an overall mean score of 3.29. Among the four dimensions, digital ethics obtained the highest score, whereas digital culture received the lowest score, although it remained within the high category. These findings suggest that students have strong competencies in accessing, evaluating, verifying, and utilizing digital information responsibly. This study concludes that digital literacy plays an important role in supporting students’ ability to assess information accuracy in complex digital environments. The findings contribute to the development of digital literacy studies in higher education and provide practical implications for strengthening digital culture and critical thinking skills in information evaluation practices.